Effects of Propofol, Low and High Doses of Remimazolam on Hemodynamic and Inflammatory Response in Laparoscopic Surgery [Letter] - Yang G; Chu Q (Dove Medical Press, 2024)
Guanyu Yang, Qinjun Chu Department of Anesthesiology and Perioperative Medicine, Zhengzhou Central Hospital Affiliated to Zhengzhou University, Zhengzhou, Henan, People’s Republic of ChinaCorrespondence: Qinjun Chu, Email jimmynetchu@163.com